‘Urban regimes’ and ‘migration regimes’: contradictions, connections and potentials - Bernt, Matthias (ERDKUNDE, 2019)
The article aims to foster a conceptual discussion about the potentials and pitfalls that emerge when the two concepts ‘migration regime’ and ‘urban regime’ are brought together. Recent developments in the field of migration studies have led to the regime concept becoming an increasingly popular strategy. Terms like ‘local migration regime’ or ‘urban migration regime’ have enjoyed growing popularity due to an expanded interest in the intersection of localities, regulation techniques and immigration. Within this debate, the ‘urban regimes’ concept has also gained increased attention.This paper argues that these are two essentially different types of regime analysis, both of which have potentials and problems. Making use of both of them in the field of migration studies requires conceptual clarity and preciseness, and will likely lead to very different findings. A synthesis of the two concepts is, therefore, not achievable, yet a careful and reflected use of them can provide new impulses both for empirical research and theory.